A short history of nearly everything - Bryson, Bill (Black Swan, 2016)
The ultimate eye-opening journey through time and space, A Short History of Nearly Everything is the biggest-selling popular science book of the 21st century and has sold over 2 million copies. 'Truly impressive...It's hard to imagine a better rough guide to science.' Guardian 'A travelogue of science, with a witty, engaging, and well-informed guide' The Times Bill Bryson describes himself as a reluctant traveller, but even when he stays safely at home he can't contain his curiosity about the world around him. A Short History of Nearly Everything is his quest to understand everything that has happened from the Big Bang to the rise of civilization - how we got from there, being nothing at all, to here, being us. Bill Bryson's challenge is to take subjects that normally bore the pants off most of us, like geology, chemistry and particle physics, and see if there isn't some way to render them comprehensible to people who have never thought they could be interested in science. As a result, A Short History of Nearly Everything reveals the world in a way most of us have never seen it before.